Pengaruh Promo Big Sale, Online Customer Review, dan Online Customer Rating Terhadap Keputusan Pembelian pada Event Tanggal Kembar Shopee - Gias Rahman Alfarisyi; Ambardi Ambardi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The purpose of this study is to determine the impact of major discount offers, online customer reviews, and online customer ratings on purchasing decisions during the Shopee twin date event. For important sales initiatives, structural equation modeling was the data analysis method used. The results show that online customer reviews have a positive but not statistically significant impact on purchasing decisions during the Shopee twin date event, even while online customer ratings have a large impact.